Super-diffusion of excited carriers in semiconductors - Ebrahim Najafi (Nature Portfolio, 2017)
Determining the spatial dynamics of excited carriers will provide a more complete understanding of ultrafast carrier dynamics in materials. Using scanning ultrafast electron microscopy, Najafiet al. are able to observe the spatiotemporal dynamics of excited electron and hole carriers in silicon.